2018
DOI: 10.1016/j.gsf.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Meso-Cenozoic tectonic evolution of the Talas-Fergana region of the Kyrgyz Tien Shan revealed by low-temperature basement and detrital thermochronology

Abstract: International audienceThis study provides new low-temperature thermochronometric data, mainly apatite fission track data on the basement rocks in and adjacent to the Talas-Fergana Fault, in the Kyrgyz Tien Shan in the first place. In the second place, we also present new detrital apatite fission track data on the Meso-Cenozoic sediments from fault related basins and surrounding intramontane basins. Our results confirm multi-staged Meso-Cenozoic tectonic activity, possibly induced by the accretion of the so-cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 114 publications
0
30
0
Order By: Relevance
“…Palaeocurrent directions during the Early Cretaceous were mainly considered to be south-directed in the basin (Figure 10a; Yang, Guo, Jiang, et al, 2017), similar to the Meso-Cenozoic foreland basins in front of the South Tianshan Orogen (Hendrix, 2000;Li et al, 2004;Li & Peng, 2010), indicating that the source area may be situated in the piedmont region of South Tianshan Orogen. Framework compositions of polymictic conglomerate and gravelly sandstone in this study have revealed that the Late Carboniferous-Permian alkali granite, F I G U R E 1 3 (a) Relative probability plots of these apatite fission-track (AFT) ages and apatite (U-Th)/He (AHe) ages across the western Tianshan Orogen showing multistage Meso-Cenozoic exhumation history (Bullen et al, 2001;Chang, Qiu, & Li, 2012;De Grave et al, 2011Dumitru et al, 2001;Glorie et al, 2010Glorie et al, , 2011Jia et al, 2015;Macaulay et al, 2013;Nachtergaele et al, 2017;Sobel, Chen, & Heermance, 2006;Sobel, Oskin, et al, 2006;Yang et al, 2014;Zhang, Li, et al, 2009;Zhang, Huang, et al, 2009); (b) Summary of AFT ages and apatite (U-Th)/He (AHe) ages of the Late Jurassic-Early Cretaceous across the western Tianshan Orogen (Bullen et al, 2001;Chang et al, 2012;De Grave et al, 2011Dumitru et al, 2001;Glorie et al, 2010Glorie et al, , 2011Jia et al, 2015;Macaulay et al, 2013;Nachtergaele et al, 2017;Sobel, Chen, & Heermance, 2006;Sobel, Oskin, et al, 2006;Yang et al, 2014;Zhang, Li, et al, 2009;Zhang, Zhu, et al, 2009;…”
Section: Sedimentary Provenancementioning
confidence: 85%
See 4 more Smart Citations
“…Palaeocurrent directions during the Early Cretaceous were mainly considered to be south-directed in the basin (Figure 10a; Yang, Guo, Jiang, et al, 2017), similar to the Meso-Cenozoic foreland basins in front of the South Tianshan Orogen (Hendrix, 2000;Li et al, 2004;Li & Peng, 2010), indicating that the source area may be situated in the piedmont region of South Tianshan Orogen. Framework compositions of polymictic conglomerate and gravelly sandstone in this study have revealed that the Late Carboniferous-Permian alkali granite, F I G U R E 1 3 (a) Relative probability plots of these apatite fission-track (AFT) ages and apatite (U-Th)/He (AHe) ages across the western Tianshan Orogen showing multistage Meso-Cenozoic exhumation history (Bullen et al, 2001;Chang, Qiu, & Li, 2012;De Grave et al, 2011Dumitru et al, 2001;Glorie et al, 2010Glorie et al, , 2011Jia et al, 2015;Macaulay et al, 2013;Nachtergaele et al, 2017;Sobel, Chen, & Heermance, 2006;Sobel, Oskin, et al, 2006;Yang et al, 2014;Zhang, Li, et al, 2009;Zhang, Huang, et al, 2009); (b) Summary of AFT ages and apatite (U-Th)/He (AHe) ages of the Late Jurassic-Early Cretaceous across the western Tianshan Orogen (Bullen et al, 2001;Chang et al, 2012;De Grave et al, 2011Dumitru et al, 2001;Glorie et al, 2010Glorie et al, , 2011Jia et al, 2015;Macaulay et al, 2013;Nachtergaele et al, 2017;Sobel, Chen, & Heermance, 2006;Sobel, Oskin, et al, 2006;Yang et al, 2014;Zhang, Li, et al, 2009;Zhang, Zhu, et al, 2009;…”
Section: Sedimentary Provenancementioning
confidence: 85%
“…The Late Jurassic–Early Cretaceous reactivation has been widely accepted based on coeval uplifting and exhumation in the western Tianshan (De Grave et al, ; Glorie et al, ) and sedimentary transformation from an extremely low‐energy, humid depositional environment, and wide source areas in the Middle Jurassic to a relatively high‐energy, semi‐arid/arid depositional environment, and local source areas in the Early Cretaceous (Jolivet et al, ; Sobel, ), in the foreland basins (Junggar, Turfan, Kuqa, and Ulugqat) on the north and south piedmonts of the western Tianshan Orogen (Li et al, ; Li & Peng, ; Li & Zeng, ; Yang et al, ). Although systematic detrital zircon U–Pb dating of Meso‐Cenozoic sequences has been conducted in the Ulugqat Basin (Yang et al, ; Yang, Guo, Jiang, et al, ), it is still controversial on the geodynamic mechanism resulting in the rapid exhumation and coarse‐grained clastic rocks sedimentation during the Late Jurassic–Early Cretaceous, as the rapid closure of Mongol–Okhotsk Ocean during the latest Jurassic–earliest Cretaceous (Nachtergaele et al, and references therein) is almost simultaneous with the collision of the Karakoram–Lhasa Block from late Middle Jurassic to Early Cretaceous (Wilhem et al, ;Yang, Guo, et al, ; Yang, Guo, & Luo, ). However, East Asia wholly entered into an escape tectonic setting in the Early Cretaceous due to the continental collision of the Karakoram–Lhasa Block at the southern margin of Asia (Yang, Guo, et al, ; Yang, Guo, & Luo, ), probably suggesting little tectonic influence of Mongol–Okhotsk Orogeny.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations